Biallelic SCN10A mutations in neuromuscular disease and epileptic encephalopathy. Issue 1 (20th December 2016) - Kambouris, Marios; Thevenon, Julien; Soldatos, Ariane; Cox, Allison; Stephen, Joshi; Ben‐Omran, Tawfeg; Al‐Sarraj, Yasser; Boulos, Hala; Bone, William; Mullikin, James C.; Masurel‐Paulet, Alice; et al.
Abstract: Objectives: Two consanguineous families, one of Sudanese ethnicity presenting progressive neuromuscular disease, severe cognitive impairment, muscle weakness, upper motor neuron lesion, anhydrosis, facial dysmorphism, and recurrent seizures and the other of Egyptian ethnicity presenting with neonatal hypotonia, bradycardia, and recurrent seizures, were evaluated for the causative gene mutation. Methods and Results: Homozygosity mapping and whole exome sequencing (WES) identified damaging homozygous variants in SCN10A, namely c.4514C>T; p.Thr1505Met in the first family and c.4735C>T; p.Arg1579* in the second family. A third family, of Western European descent, included a child with febrile infection‐related epilepsy syndrome (FIRES) who also had compound heterozygous missense mutations in SCN10A, namely, c.3482T>C; p.Met1161Thr and c.4709C>A; p.Thr1570Lys. A search for SCN10A variants in three consortia datasets (EuroEPINOMICS, Epi4K/EPGP, Autism/dbGaP) identified an additional five individuals with compound heterozygous variants. A Hispanic male with infantile spasms [c.2842G>C; p.Val948Leu and c.1453C>T; p.Arg485Cys], and a Caucasian female with Lennox–Gastaut syndrome [c.1529C>T; p.Pro510Leu and c.4984G>A; p.Gly1662Ser] in the epilepsy databases and three in the autism databases with [c.4009T>A; p.Ser1337Thr and c.1141A>G; p.Ile381Val], [c.2972C>T; p.Pro991Leu and c.2470C>T; p.His824Tyr], and [c.4009T>A; p.Ser1337Thr and c.2052G>A; p.Met684Ile]. Interpretation: SCN10A is a member of the voltage‐gated sodium channel (VGSC) gene family. Sodium channels are responsible for the instigation and proliferation of action potentials in central and peripheral nervous systems. Heterozygous mutations in VGSC genes cause a wide range of epileptic and peripheral nervous system disorders. This report presents autosomal recessive mutations in SCN10A that may be linked to epilepsy‐related phenotypes, Lennox–Gastaut syndrome, infantile spasms, and Autism Spectrum Disorder.